2008
DOI: 10.1016/j.jacc.2007.09.041
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Magnetic Resonance Imaging Study for Quantification of Infarct Size Comparing Directly Serial Versus Single Time-Point Measurements of Cardiac Troponin T

Abstract: All single-point cTnTs, except on admission, give a good estimation of infarct size and perform as well as peak cTnT or AUC cTnT. Infarct estimation by single-point measurements, particularly cTnTD4, may gain clinical acceptance because the measurement is easy and inexpensive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
83
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 164 publications
(97 citation statements)
references
References 33 publications
10
83
4
Order By: Relevance
“…Furthermore, Troponin within the first days after STEMI without OHCA is associated with infarct size, left ventricular function as well as mortality in several studies [20][21][22]. However, in the present study hs-TnT did not predict death due to cardiovascular causes or multi-organ failure in the group without STEMI.…”
Section: Discussioncontrasting
confidence: 80%
“…Furthermore, Troponin within the first days after STEMI without OHCA is associated with infarct size, left ventricular function as well as mortality in several studies [20][21][22]. However, in the present study hs-TnT did not predict death due to cardiovascular causes or multi-organ failure in the group without STEMI.…”
Section: Discussioncontrasting
confidence: 80%
“…The maximal cTnT value (obtained typically on day 1) was closely correlated with the value from day 3, reported to correlate best with magnetic resonance imaging-determined infarct size. 33,34 Thus, our data are consistent with the association between the size of MI and outcomes, particularly among incident cases, and underscore that maximal cTnT value measured clinically can be used as a suitable indicator of MI severity.…”
Section: Discussionsupporting
confidence: 83%
“…37 In addition, there are data linking cTnT level measured at 72 hours after MI to infarct size, regardless of reperfusion status. 33,34 Finally, previous studies have shown that troponin elevation was associated with subsequent cardiac events in patients with acute coronary syndromes, probably as a reflection of severe anatomical disease. [3][4][5][6][7][8] However, several important limitations of previous studies hinder their clinical applicability.…”
Section: Prognostic Value Of Ctnt Post-mimentioning
confidence: 98%
“…cTnT have characteristic higher molecular weight, higher fraction of unbound cTnT, less degradation, whereas cTnI is more frequently found as binary or tertiary complex in blood. Previous studies proves that early appearing troponin pool may give information on the quality of microvascular reperfusion, while the concentration of cTn on Day 3 or 4 reflects myocardial infarct size [2].…”
Section: Introductionmentioning
confidence: 95%